Fabricating model heterostructures of large-area monolayer or bilayer MoS2 on an Au(111) surface under ultra-high vacuum - Bingrui Li; Weiwei Huang; Chaoqi Dai; Boyuan Wen; Yan Shen; Fei Liu; Ningsheng Xu; Fangfei Ming; Shaozhi Deng (Results in Physics)
Fabricating heterojunctions with precisely controlled interfacial structures is crucial for exploring novel low-dimensional physics and for realizing high-performance devices. However, such capabilities are often constrained by contamination from the ambient environment or by the limitations of applicable methods and materials under vacuum conditions. In this study, MoS2/Au(111) heterostructures were fabricated by exfoliating MoS2 thin layers onto a crystallized Au(111) surface using a gold-assisted exfoliation method in an ultra-high vacuum environment. This method yields millimeter-sized monolayer or sub-millimeter-sized bilayers with contamination-free interfaces, which are unattainable for samples made in air. Scanning tunneling microscopy revealed that both the monolayer and the bilayer exhibit uniform and well-ordered moiré superlattices controlled by the twisting angle between the Au(111) surface and the MoS2 overlayer. The direct contact with the Au surface renders the monolayer MoS2 weakly metallic, while a less coupled bilayer is semiconducting, indicating a 0.54 eV Schottky barrier for the MoS2/Au(111) contact. This method is applicable to various combinations of van der Waals materials and metal surfaces. The uniform and controllable heterojunctions can serve as ideal model systems for exploring semiconductor–metal interfaces and atomic structures formed within.